Effect of cinnamon, turmeric and black cumin seed supplementation on growth performance, carcass composition and meat quality of Japanese quail - Abd Rahman, Asmaa Husnaa (2015)
The objective of this study was to evaluate the effect of herbs supplementation on growth performance and carcass composition of Japanese quail (Coturnix japonica). The reduction in the use of antibiotic as a growth promoter due to concern of bacterial resistance has initiated the utilization of herbs in poultry diets. This study was conducted at Universiti Putra Malaysia and used 120 one-day old Japanese quail which were randomly divided into four treatment groups with three replicates each in a completely randomize design. One group served as a control group (T1) that received the basal diet and the rest three experimental diets consisted of the basal diet with addition of 0.5% of cinnamon (T2), 0.5% turmeric (T3) and 0.5% black cumin seed (T4). The body weight gain and feed intake were recorded weekly. The feed conversion ratio (g feed/ g weight gain) was then calculated by dividing the feed intake with body weight gain. At the end of the 42-day feeding period, the quails were slaughtered and the relative weight of gastro-intestinal tract, liver and gizzard measured. The weight of hot carcass was recorded and then the dressing percentage of quail for each treatment was calculated. Following that, meat and bone of carcass was been separated to determine meat to bone ratio for each replicate. The breast muscle was taken from carcass to analyze meat quality of quail for each treatment. Meat quality was analyzed based on drip loss, cooking loss, color and tenderness of quail. For growth performance, the total feed intake, body weight gain and feed conversion ratio showed significant increases (P<0.05) due to the supplementation of herbs. Carcass composition, dressing percentage, liver and gizzard showed no significant different between (P>0.05) the treatments. But for meat to bone ratio and gastro-intestinal tract showed significant (P<0.05) between the treatments. For meat quality, drip loss, cooking loss and shear force did not show significant different between the treatment (P>0.05) but color of meat show significant different between the treatments (P<0.05). Under condition of this study, it was concluded that herbs has a potential in improving the quail performance in growth, carcass composition and meat quality. Further research to investigate the growth performance and carcass composition of Japanese quail by supplemented with herbs in feed was recommended.